(untitled) (Sains Humanika, 2011)
The story of prophets in Egypt as recorded in the Quran contains plenty of lessons particularly according to management perspectives. There are elements of management derived from the story of the prophets such as setting of objective, planning, leadership, controlling as well as communication. These useful lessons act as guider to those who involve in the field of management in Malaysia especially to form world view of Islamic management, epistemology and commanding good and forbidding evil in processing of management. Management from Quranic perspective is an alternative toward current management that highly practice based on western paradigm.